Pemanfaatan Video Pembelajaran dalam Meningkatkan Motivasi Belajar Mahasiswa pada Mata Kuliah Biologi Dasar - Syafruddin, Wardatul Jannah; Nugraha, Fadel (Program Studi Pendidikan Biologi, FKIP, Universitas Nusa Nipa, 2025)
Complex Basic Biology course materials and learning processes that still use manual textbooks make it difficult for students to follow the learning process on campus. Learning videos are audio-visual media used to deliver educational or training materials in an interesting and effective way. Through learning videos, the delivery of information becomes more interactive, attracts attention, and makes it easier to understand complex concepts. Biology learning videos are made with the aim of making it easier for students to understand the material so that they can increase their interest and motivation in learning biology, especially Basic Biology courses. This study involved 76 undergraduate biology students taking a Basic Biology course. It used both qualitative and quantitative methods. Data was collected through a questionnaire where students evaluated the learning videos. The validity test showed a significant value of 0.00 < 0.05, and the reliability test gave a value of 0.074 > 0.07, meaning the questionnaire was valid and reliable. The results of the data analysis showed that more than 80% of students agreed and strongly agreed that the biology learning videos helped them understand the material better. In conclusion, learning videos can increase students' interest and motivation in studying biology, especially in Basic Biology courses.